Negative Pressure Pulmonary Edema: A Case Report - Budhathoki, Anisha (JNMA J Nepal Med Assoc, 2020)
Negative pressure pulmonary edema is an uncommon complication of the extubation of the endotracheal tube. An increase in intrathoracic pressure and negative pressure of the lung caused by acute laryngeal spasm results from acute upper respiratory obstruction causing life-threatening pulmonary edema by alveolar-capillary damage is called negative pressure pulmonary edema. We here describe 28-years old female case the preoperative diagnosis of pelvic inflammatory disease undergoing exploratory laporoscopy caused negative pressure pulmonary edema while extubation. With the immediate treatment, the patient was discharged without any abnormalities.